Super toughened immiscible poly(l-lactide)/poly(ethylene vinyl acetate) (PLLA/EVA) blend achieved by in situ cross-linking reaction and carbon nanotubes - Wang, Xiong-fei; He, Zhen-zhen; Yang, Jing-hui; Zhang, Nan; Huang, Ting; Wang, Yong; Zhou, Zuo-wan (Composites. Part A, Applied science and manufacturing, 2016)
Toughening modification is always one of the main subjects of structural materials. A small quantity of dicumyl peroxide (DCP) and carbon nanotubes (CNTs) were simultaneously introduced into an immiscible poly(l-lactide)/poly(ethylene vinyl acetate) (PLLA/EVA) blend through melt compounding processing. The presence of chemical cross-linking structure in the polymer components and the physical network of CNTs were demonstrated through a series of direct and indirect characterization methods. The results demonstrated that DCP and CNTs exhibited synergistic toughening effects and the dynamically vulcanized blend composites exhibited excellent impact toughness. This work provides an alternative way to improve the impact toughness of an immiscible polymer blends.